A complex regional intervention to implement advance care planning in one town's nursing homes: Protocol of a controlled inter-regional study - Briggs Linda; Hammes Bernard J; Rixen Stephan; Mellert Christine; Rothärmel Sonja; in der Schmitten Jürgen; Wegscheider Karl; Marckmann Georg (BMC, 2011)
Abstract Background Advance Care Planning (ACP) is an emerging strategy to ensure that well-reflected, meaningful and clearly documented treatment preferences are available and respected when critical decisions about life-sustaining treatment need to be made for patients unable to consent. In Germany, recent legislation confirms that advance directives (AD) have to be followed if they apply to the medical situation, but implementation of ACP has not yet been described. Methods/Design In a longitudinal controlled study, we compare 1 intervention region (4 nursing homes [n/hs], altogether 421 residents) with 2 control regions (10 n/hs, altogether 985 residents). Inclusion went from 01.02.09 to 30.06.09, observation lasted until 30.06.10. Primary endpoint is the prevalence of ADs at follow-up, 17 (12) months after the first (last) possible inclusion. Secondary endpoints compare relevance and validity of ADs, process quality, the rate of life-sustaining interventions and, in deceased residents, location of death and intensity of treatment before death. The regional multifaceted intervention on the basis of the US program Respecting Choices® comprises training of n/h staff as facilitators, training of General Practitioners, education of hospital and ambulance staff, and development of eligible tools, including Physician Orders for Life-Sustaining Treatment in case of Emergency (POLST-E). Participation data: Of 1406 residents reported to live in the 14 n/hs plus an estimated turnover of 176 residents until the last possible inclusion date, 645 (41%) were willing to participate. Response rates were 38% in the intervention region and 42% in the control region. Non-responder analysis shows an equal distribution of sex and age but a bias towards dependency on nursing care in the responder group. Outcome analysis of this study will become available in the course of 2011. Discussion Implementing an ACP program for the n/hs and related health care providers of a region requires a complex community intervention with the effect of nothing less than a cultural shift in this health care sector. This study is to our knowledge the first to develop a strategy for regional implementation of ACP, and to evaluate its feasibility in a controlled design. Trial Registration ISRCTN: ISRCTN99887420